1998
DOI: 10.1095/biolreprod58.3.857
|View full text |Cite
|
Sign up to set email alerts
|

Replication of Cytopathic and Noncytopathic Bovine Viral Diarrhea Virus in Zona- Free and Zona-lntact In Vitro-Produced Bovine Embryos and the Effect on Embryo Quality1

Abstract: The aim of the present study was to determine whether or not cytopathic (CP) and noncytopathic (NCP) bovine viral diarrhea virus (BVDV) are able to replicate within in vitro-produced embryos and to investigate whether inoculation of embryos with BVDV affects their normal development. Zona pellucida (ZP)-free oocytes, zygotes, 8-cell-stage embryos, morulae, and hatched blastocysts (HB) were incubated for 1 h in 1 ml of Minimal Essential Medium containing 10(6.00) tissue culture infectious dose (TCID)50/ml NCP B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 45 publications
1
29
0
1
Order By: Relevance
“…It might therefore be possible to conclude that the stage from the mature oocyte to the 2-cell embryo or 4-cell embryo stage is not susceptible to NCP BVDV. The virus titer of hatched blastocysts was low, the same as in the results reported by Vanroose et al [10], but in our study the virus could be isolated from two samples at 24 hr, findings that differed from theirs, and we clearly demonstrated the presence of NCP BVDV specific antigen in hatched blastocysts ( Fig. 1.-b).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…It might therefore be possible to conclude that the stage from the mature oocyte to the 2-cell embryo or 4-cell embryo stage is not susceptible to NCP BVDV. The virus titer of hatched blastocysts was low, the same as in the results reported by Vanroose et al [10], but in our study the virus could be isolated from two samples at 24 hr, findings that differed from theirs, and we clearly demonstrated the presence of NCP BVDV specific antigen in hatched blastocysts ( Fig. 1.-b).…”
supporting
confidence: 90%
“…These findings suggest that the 2-and 4-cell embryos are not susceptible to NCP BVDV and that they acquire susceptibility to the virus when they develop into the hatched blastocysts. Vanroose et al [10] recently reported that mature oocytes and fertilized ova could not be infected with NCP BVDV. It might therefore be possible to conclude that the stage from the mature oocyte to the 2-cell embryo or 4-cell embryo stage is not susceptible to NCP BVDV.…”
mentioning
confidence: 99%
“…Reportedly, morula and blastocyst, hatched and freed in the pellucid zone, are more susceptible to bovine herpesvirus-1 (IBR) (Vanroose et al 1997, Graham 2013, and bovine viral diarrhea BVD virus (Vanroose et al 1998, Lanyon et al 2014. Therefore, in this study, the presence of an infectious agent as a cause for some of the losses can be inferred.…”
Section: Discussionmentioning
confidence: 90%
“…This inhibitory effect was not due to virus replication in the embryonic cells, since an intact zona pellucida acts as a protective barrier against BoHV-1 ( Vanroose et al 1997Vanroose et al , 1998. Therefore, other reasons need to be established to explain the adverse effect of BoHV-1 on embryonic development.…”
Section: Discussionmentioning
confidence: 99%